An Incidental Finding of Whipple’s Disease Masquerading as Nonspecific, Long-Standing Symptoms - Thomas Tuggle; Alison I. Orvin; Christian Caveness; Christopher Ingram (Case Reports in Infectious Diseases)
Whipple’s disease is a rare bacterial infection that is often present for years prior to diagnosis. Symptoms are nonspecific in the early stages of presentation and are primarily gastrointestinal in nature. The disease may progress with more systemic symptoms including arthralgia, fever, lymphadenopathy, cardiovascular disease, and central nervous system involvement. This case describes a man with a history of long-standing, nonspecific symptoms who only began to show significant improvement after an incidental finding of Whipple’s disease. Due to its rare nature, other instances of the disease have likely gone undiagnosed. A brief review of relevant literature is also included.